Pengaruh Kegiatan Mencocok Gambar terhadap Perkembangan Motorik Halus Anak di RA Darun Najah - Uswatun Hasanah; Vina Fauziah Asyri; Usep Dimyati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of picture matching activities on the development of children's fine motor skills at RA Darun Najah. Fine motor skills are skills that involve coordination between small muscles, especially the hands and fingers, which play an important role in children's daily activities and academic readiness. Picture matching activities were chosen as a method to train children's fine motor skills through fun, creative, and educational activities. This study used a quantitative approach with an experimental design involving samples of early childhood children at RA Darun Najah. The instruments used were observation and assessment of fine motor skills before and after participating in picture matching activities. The results showed that there was a significant effect of picture matching activities on improving children's fine motor skills, such as grasping skills, placing objects with precision, and hand-eye coordination. In addition, this activity also contributed to improving children's concentration, focus, and problem-solving abilities. Based on these findings, it can be concluded that picture matching activities are an effective method in supporting the development of fine motor skills in early childhood children at RA Darun Najah.